2019
DOI: 10.4187/respcare.07026
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Academic Intensivists' Use of Neuromuscular Blockade in Subjects With ARDS

Abstract: BACKGROUND: Our Cooling to Help Injured Lungs (CHILL) trial of therapeutic hypothermia in ARDS includes neuromuscular blockade (NMB) as an inclusion criterion to avoid shivering. NMB has been used to facilitate mechanical ventilation in ARDS and was shown to reduce mortality in the ACURASYS trial. To assess the feasibility of a multi-center CHILL trial, we conducted a survey of academic intensivists about their NMB use in patients with ARDS. METHODS: We distributed via email a 16-question survey about NMB use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 37 publications
2
13
0
Order By: Relevance
“…Importantly more than one in three respondents reported having treated >10 patients in the year with 10% having delivered PP to more than 20 patients in the year of the survey. The duration and frequency of PP sessions were in keeping with a recent large prospective multicentre prevalence study which found the duration of the first PP session was 18 (16)(17)(18)(19)(20)(21)(22)(23) h. The findings of our survey are consistent with increased use of PP in patients with moderate to severe ARDS. The increasing use of PP amongst the referral centres was encouraging.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Importantly more than one in three respondents reported having treated >10 patients in the year with 10% having delivered PP to more than 20 patients in the year of the survey. The duration and frequency of PP sessions were in keeping with a recent large prospective multicentre prevalence study which found the duration of the first PP session was 18 (16)(17)(18)(19)(20)(21)(22)(23) h. The findings of our survey are consistent with increased use of PP in patients with moderate to severe ARDS. The increasing use of PP amongst the referral centres was encouraging.…”
Section: Discussionsupporting
confidence: 89%
“…This attitude and practice reflects both the evidence that NMB can help some patients with moderate and severe ARDS 18,19 and the evidence from recent survey where it was found that NMB was used frequently to facilitate mechanical ventilation in patients with moderate to severe ARDS. 20 However, the fact that NMB is not routinely used is consistent with the recently published ROSE trial, 21 which showed that the systematic use of NMB does not appear to improve outcome.…”
Section: Discussionsupporting
confidence: 67%
“…1 It is beyond the scope of this review to comment on the usefulness of profound NMB during ventilation of severe ARDS patients. 33,34 NMB is certainly needed at the time of endotracheal intubation as well as during invasive mechanical ventilation to improve oxygenation, 33 to correct patient-ventilator asynchrony, [34][35][36][37] to reduce the work of breathing, 1,24,38 and to reduce the driving pressure. 39 Prolonged NMB increases the incidence of neuromuscular weakness and critical illness neuropathy, which could delay the weaning process and cause various problems during the rehabilitation.…”
Section: Monitoring Nmbmentioning
confidence: 99%
“…A neuromuscular blockade used for 1–2 days is thought to be beneficial in selected patients with ARDS, mainly by reducing patient‐ventilator dyssynchrony 42,43 . It was the most commonly used adjunctive therapy (22%) for moderate to severe ARDS in the LUNG SAFE study 43 .…”
Section: Methodsmentioning
confidence: 99%